Labor conflicts in the industrial sector during the seventies.: The case of the workers of the meat plants of Berisso 1969-1972. - Nava, Agustín (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2018)
This paper is inscribed within of studies on the history of the labor movement during the years '60s and '70s in Argentina and aims to analyze the union dynamics and the labor conflict of a particular actor within the labor movement of the Gran La Plata region: the workers of meat the Swift and Deltec located in Berisso. Through both a quantitative and qualitative analysis, developed from newspaper sources, the Informes Laborales del Servicio de Documentación e Información Laboral (DIL)  and Archivo de la Dirección de Inteligencia de la Policía de Buenos Aires (DIPBA), we will focus on the dynamics presented by labor unrest, in the situation that the industry in which these workers were inserted, the internal organization of the trade unions studied, the trade union dynamics and alignment, and the specific modalities with which the State and the employers intervened in them. The purpose of this analysis is to be able to make complex certain readings and general interpretations about the period in particular, as well as to deepen on topics and dimensions referring to the characteristics and dynamics of the workers movement in general.